Does ductal adenocarcinoma of the prostate (DA) have any prognostic impact on patients with de novo metastatic prostate cancer?. Issue 14 (21st August 2019) - Wu, Tao; Zhao, Jinge; Liu, Zhenhua; Shen, Pengfei; Zhang, Mengni; Sun, Guangxi; Liu, Jiandong; Liao, Banghua; Chen, Junru; Zhu, Sha; Dai, Jindong; Wang, Zhipeng; et al.
Abstract: Background: The prognostic value of ductal adenocarcinoma of the prostate (DA) in nonmetastatic prostate cancer (PCa) has been identified in many studies. However, it remains unknown whether DA is an adverse prognostic factor in metastatic PCa (mPCa). Method: Data from 634 mPCa patients histopathologically documented with DA or/and acinar adenocarcinoma of the prostate in our center between 2012 and 2018 were retrospectively analyzed. Propensity score matching (PSM) was used to balance the baseline features. Data from the Surveillance, Epidemiology, and End Results (SEER) database were utilized to validate our findings. Castration‐resistant PCa‐free survival (CFS), overall survival (OS), and cancer‐specific survival (CSS) were set as endpoints. Results: DA was confirmed in 35 of 634 (5.5%) patients. Among the DA‐positive patients, 7 of 35 (20%) and 28 of 35 (80%) harbored high (DA ≥ 50%) and low (DA < 50%) DA components, respectively. DA was not associated with poorer median CFS (mCFS) or median OS (mOS) either before PSM (mCFS: 16.9 vs 18.4 month, P  =   .814; mOS: 42.0 vs 70.1 month, P  =   .796) or after PSM (mCFS: 16.9 vs 16.9 month, P  =   .949; mOS: 42.0 vs 79.9 month, P  =   .960). Likewise, in the SEER data, DA‐positive patients (n = 15 153) shared similar median CSS (25.0 vs 28.0 month, P  =   .206) and OS (26.0 vs 35.0 month, P  =   .095) with DA‐negative patients (n = 70). No prognostic difference was found between patients with high and low DA components. Conclusion: We conducted the first study investigating the prognostic value of DA in de novo mPCa. DA was not associated with adverse clinical outcomes in mPCa patients. These findings are helpful for prognostic evaluation, treatment decision making and counseling in mPCa patients.